Analysis of Earning Asset Quality Relation to Profitability at PT. Regional Development Bank (BPD) Central Sulawesi - Guasmin Guasmin (Universitas Muhammadiyah Palu, 2022)
PT. The Regional Development BANK (BPD) of Central Sulawesi is a regionally-owned enterprise. The existence of PT. The Regional Development BANK (BPD) of Central Sulawesi as a regional company has become a Trusted bank in Indonesia, Healthy, Developing, Developing Competitive, Appropriate Technology and Contributing to the Economic Growth of Central Sulawesi. This study reveals that the allowance for possible losses on earning assets is the part prepared to cover the risk of default from classified earning assets. With PPAP, the Company is able to minimize losses that are greater than losses caused by uncollectible productive assets. And the company's profitability is strongly influenced by the quality of its productive assets (because the company's main source of income comes from productive assets), quality productive assets are assets with a small default rate and the existing failure to pay can be covered by the level of prepared reserve funds (PPAP).